KLF4 is an epigenetically modulated, context-dependent tumor suppressor - Frazzi, Raffaele (Frontiers in Cell and Developmental Biology, 2024)
Eliminato: promoter (as in the case of HNSCC) 320 Eliminato: suppressor (as in the case of NHL and colon cancer) 321 Eliminato: Among the most relevant epigenetic modifications there 322 is cytosine methylation in position 5 of the DNA (5mC), which is 323 also relevant in directing the TF binding specificity [54]. 324 Furthermore, the product of 5mC oxidation (5hmC) recruits 325 chromatin remodelling complexes onto DNA. The B-cell 326 reprogramming into iPSC is accompanied by an almost complete loss 327 of 5mC, with a concomitant increase in 5hmC [54]. The sustained 328 5hmC conversion corresponds to an enrichment of specific TFs onto 329 gene regulatory elements (GRE) related to pluripotency and/or 330 genome topology, including KLF4. Furthermore, the demethylation 331 of the core pluripotency TFs (OSKM) leads to their activation.